2009
DOI: 10.1097/01.hp.0000363842.62922.58
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial Study of the Risk of Lung Cancer among French Uranium Miners: Radon, Smoking and Silicosis

Abstract: This case-control study nested in the French cohort of uranium miners provides an opportunity to take account of silicosis and smoking in the assessment of the relation between radon and lung cancer. The study includes 100 miners who died of lung cancer and 500 matched controls born within the same period of birth and of the same age at the time of death of the matching case. Data on radon exposure are obtained from individual monitoring of the miners, and data on smoking come from medical records and intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Recognised comorbid conditions such as COPD are independent risk factors regardless of smoking status 25. Additionally, unrecognised factors such as environmental tobacco smoke, radon, occupational exposures and diet may contribute to the development of lung cancer in smokers and non-smokers 5 17 26 27. This unique study of the familial clustering of lung cancer using a population-based resource linking genealogy, a tumour registry and DC data begins to clarify the role of genetics in non-smoking-related lung cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognised comorbid conditions such as COPD are independent risk factors regardless of smoking status 25. Additionally, unrecognised factors such as environmental tobacco smoke, radon, occupational exposures and diet may contribute to the development of lung cancer in smokers and non-smokers 5 17 26 27. This unique study of the familial clustering of lung cancer using a population-based resource linking genealogy, a tumour registry and DC data begins to clarify the role of genetics in non-smoking-related lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…While cigarette smoking is well established as the strongest risk factor for the development of lung cancer, environmental and genetical factors are suspected to play a role 4 5. Studies have shown familial clustering of lung cancer cases, supporting evidence for a genetical contribution to the development of lung cancer 6–12.…”
Section: Introductionmentioning
confidence: 99%
“…30-8.22) was also reported in the ceramics manufacturing (Scarselli et al 2011). Many studies have provided strong evidence for linking chronic inflammation resulting in fibrosis and lung damage to increased excess mortality from lung cancer risk in silicosis (Amabile et al 2009;Le Jeune et al 2007;Soutar et al 2000). Spigno et al (2007) reported that lung cancer risk was elevated among patients with silicosis, especially for those who smoke.…”
Section: Epidemiological Perspectivesmentioning
confidence: 98%
“…While cigarette smoking is well established as the strongest risk factor for the development of lung cancer, environmental and genetic factors are suspected to be involved (Sun et al, 2007;Amabile et al, 2009). Although cigarette smoke, which contains numerous chemicals, increases the risk of various lung diseases, including lung cancer and contributes to premature death (Nyunoya et al, 2014), the molecular mechanisms by which it causes cancer remain to be established.…”
Section: Introductionmentioning
confidence: 98%